Cost Comparison of General Anesthesia and Regional Anesthesia in Hand and Forearm Surgery. - Akman, Damla; Subaşi, Ferhunde Dilek; Deligöz, Özlem; Ekinci, Osman (International Medical Journal, 2023)
Introduction: Economics is gaining importance all over the world. The high costs of health expenditures prompt preference for less costly methods in health practices. General and regional anesthesia are both commonly preferred methods in upper extremity surgery. In our study, we aimed to compare the cost of general or regional anesthesia in patients scheduled for hand and forearm surgeries. Methods: The study was conducted in the Department of Anesthesiology and Reanimation, XXX Hospital, after ethics committee approval. Our study included 69 patients aged 18 years and older with ASA (American Society of Anesthesiologists) classification I-II-III who were planned for hand and forearm surgery. Patients were divided into two groups: infraclavicular block (ICB) and general anesthesia (GA). Ultrasonography-guided infraclavicular block was performed in the ICU group. The GA group underwent general anesthesia. For both groups, the patient's arrival time to the room, anesthesia starts and end time, and surgery start, and end time were recorded. Intraoperative and postoperative medications and consumables used for the patient were recorded. Results: Comparing the two groups, the total intraoperative cost was found to be significantly lower in the ICB group than in the GA group (p < 0.05). Surgery durations were similar in both groups. Anesthesia control time, total anesthesia time, patient stay in the room and postoperative recovery room follow-up time were found to be statistically significantly shorter in the ICB group compared to the GA group (p<0.05). Conclusion: We concluded that regional anesthesia is more advantageous than general anesthesia in terms of cost in hand and forearm surgeries.